Circular Economy in Retail Spaces: Behavioral Drivers Of Mall ‎Selection in Malaysia - Shina, Aminath; Wong, Ling Chai; Ahmad, Rohizan; Tee, Poh Kiong; Hasim, Halina; Wong, Siao Fui (International Journal of Accounting and Economics Studies, 2026)
Kuala Lumpur’s retail sector, with revenue reaching 142.5 billion in August 2023, includes over 20 large shopping malls integrating Circular Economy (CE) practices to enhance sustainability. CE focuses on minimizing waste and maximizing resource efficiency through reusing, ‎recycling, and composting. This study examines the impact of CE initiatives on consumer behavior in these malls, utilizing primary data ‎from 614 respondents across 9–10 high-traffic malls. The research measures consumer awareness, preferences, engagement, loyalty, and ‎satisfaction with CE practices. Preliminary findings indicate that consumer awareness, engagement, and satisfaction significantly influence ‎mall selection, while preferences and loyalty show negligible impact. Applying the Theory of Planned Behavior, the study highlights the ‎importance of promoting environmental benefits, consumer responsibility, and empowering consumers through education and accessible ‎participation options. This research offers critical insights for mall developers, retailers, and policymakers, aiding them in aligning strategies ‎with growing consumer inclinations towards sustainability. By focusing on Kuala Lumpur, the study contributes a regional perspective to ‎the global discourse on sustainable retail, fostering a more environmentally responsible retail environment.